Character-Based Arabic Language Learning Assessment Innovation - Homaidah; M. Yunus Abu Bakar (Raja Zulkarnain Education Foundation, 2025)
Assessment in education is the most crucial component for measuring student learning outcomes. Arabic language learning has experienced a paradigm shift from a focus solely on cognitive aspects to a holistic assessment oriented toward character development. This means that students are unable to understand and practice religious values related to moral ethics in school life, such as disrespect toward teachers, increased bullying, fights between students, smoking on school grounds, and various other unethical behaviors. This has led to a tendency to neglect character education as a priority. Therefore, innovations in Arabic language education are needed that integrate and prioritize strengthening student character. Therefore, character-based Arabic language learning assessment innovations are presented as an integrative effort that combines language proficiency with character values such as honesty, responsibility, discipline, and cooperation. The innovation in character-based Arabic language assessment aims to develop an evaluation method that not only measures linguistic competence but also shapes students' personalities with noble morals and the ability to become responsible individuals. The developed teaching system combines assessment of language skills (Istima', Kalam, Qiro'ah, Kitabah) with observation of character values such as honesty, responsibility, cooperation, and discipline. The method used is a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. Results indicate that the implementation of character-based assessment can increase learning motivation, active student engagement, and create a more meaningful and holistic learning environment. This innovation is expected to make a real contribution to the development of more humanistic Arabic language learning evaluations relevant to national character education goals.